Increasing Capability, Resilience, Self Leadership, and Employee Engagement on Employee Performance as Intervernal Variables at PT. IMR ARC STEEL - Mahargi Rizki Hutomo; Siti Mujanah; Sumiati (PT Inovasi Pratama Internasional, 2023)
This research was conducted to analyze IT Capability, Resilience, Self Leadership and Employee Engagement on employee performance as intervening variables at PT.IMR ARC STEEL. This study used the quantitative method of PLS version 3 and SPSS tools. Primary data sources using questionnaires or questionnaires. The population in this study were 70 employees. The sampling technique used is probability sampling technique. The analytical tools used include validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, F tests, t tests, and tests of the coefficient of determination. The results of the statistical analysis explain that: (1) IT Capability has a negative effect on employee engagement on employee performance (2) IT Capability on employee performance at PT.IMR AMR ARC STEEL, which means that it has a significant negative effect if employees have good IT Capability, then employee performance will be higher. (3) Resilience has an effect on employees engagement at PT. IMR ARC STEEL. The researcher determines the effect of self-leadership on employee engagement that the variables of resilience and employee engagement have a weak but positive relationship, meaning that if resilience increases, employee engagement will increase. (4) Resilience affects employee performance at PT. IMR ARC STEEL resilience variable has a positive and significant impact on employee performance at PT. IMR ARC STEEL. (5) Self leadership influences employee engagement at PT. IMR ARC STEEL. Researchers established the effect of self-leadership on employee engagement that when employees have a high level of self-leadership, they will really feel excited and involved in their own work. (6) Self leadership has a significant positive effect on employee performance. (7) The significant negative effect of employee engagement on employee performance is proven.